The Effect of Photopriode Differences on Chlorella sp. With Continuous Photobioreactor System - Hendra Pranata Napitupulu; Sukendi Sukendi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted in March 2019 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. Pekanbaru. The purpose of this study was to determine the best photoperiod in increasing the growth rate and biomass production of Chlorella sp. with a photobioreactor system with LED lights (Light Emitting Diode). The method used in this research was experimental using Completely Random Design (CRD) one factor with four treatments and repeated three times. The treatments used was P1 (24 bright - 0 dark), P2 (20 bright - 04 dark), P3 (16 bright - 08 dark), P4 (12 bright - 12 dark). Cultivation was carried out for ten days, using Dahril Fertilizer Solution. The results showed that the treatment of the dark cycle and the light cycle affected the population density and specific growth rate. Lighting 16 hours Bright - 08 hours Dark gave the best results with a cell density of 643.33 x 104 cells / ml and a specific growth rate of 0.1966 / day with peak growth occurring on the day eight. Water quality parameters during the study were optimal for the growth of Chlorella sp.with a water temperature of 29-33 0C, pH 7-8.9 and dissolved oxygen 8-8.5 mg / l. Keywords: Photopriode, Photobioreactors, Chlorella sp.